The Influence of Brand Awareness, Brand Image, and Price on the Purchase Decision of Pucuk Harum Tea: A Survey Study of Consumers in Jepara Regency - Ameliana, Dea; Huda, Nurul (Golden Ratio of Marketing and Applied Psychology of Business, 2026)
This study aims to analyze the influence of brand awareness, brand image, and price on the purchase decision of Teh Pucuk Harum in Jepara Regency. This study is motivated by previous research findings that show differences in the relationship between brand awareness, brand image, and price on purchasing decisions. The method employed is a quantitative approach, utilizing a survey technique through an online questionnaire, with 110 respondents who are consumers of Teh Pucuk Harum in Jepara Regency. The sampling method employed is purposive sampling, targeting individuals aged 17 to 40 years residing in Jepara Regency who are familiar with and consume Teh Pucuk Harum. Data analysis was conducted using the Partial Least Squares (PLS) method with SmartPLS 3.0 software. The study findings reveal that Brand Image and Price positively and significantly influence the Purchase Decision of Teh Pucuk Harum in Jepara Regency. In contrast, Brand Awareness shows a negative and non-significant impact on the purchase decision.